Distribution and partitioning of polybrominated diphenyl ethers in sediments from the Pearl River Delta and Guiyu, South China. (April 2018) - Huang, Youda; Zhang, Dainan; Yang, Yu; Zeng, Xiangying; Ran, Yong
Abstract: Polybrominated diphenyl ethers (PBDEs) were investigated by GC–NCI–MS in sediments collected from the Pearl River Delta (PRD) and Guiyu town, South China. The concentrations of ∑39 PBDEs and BDE 209 were in the ranges of 0.31–38.9 ng g −1 and 12.2–488 ng g −1 in the PRD, and 2.57–21, 207 ng g −1 and 7.02–66, 573 ng g −1 in Guiyu, respectively. The levels of PBDEs in Dongjiang River (DJ), Zhujiang River (ZJ), and Beijiang River (BJ), and Guiyu (GY) followed the order: GY > DJ > ZJ > BJ. The very high PBDE concentration (87, 779 ng g −1 ) was detected at G1 sediment in Guiyu compared with those in sediments from other regions around the world. The PBDE mixtures detected were mainly comprised of penta-, octa-, and deca-BDEs, in which deca-BDE was the dominant constituent. The abundant congeners, excluding BDE-209, were BDE-47, BDE-99, and BDE-183, suggesting the diverse use of commercial products containing these congeners in this region. The concentrations of major congeners were significantly correlated with total organic carbon (TOC) contents ( p  < .01). A good regression between the logarithmic TOC-normalized BDE average concentrations and their log K ow confirmed that the sorption of PBDEs on sediment organic matter governed their spatial distribution, transport, and fate in the sediments. Furthermore, risk quotients (RQs) derived from concentrations of PBDEs in sediments from our study may pose high ecological risks to exposure of benthic organisms. Graphical abstract: Image 1 Highlights: The concentrations of PBDEs in sediments from Guiyu sites (an e-waste site) are very high. Partitioning of PBDEs on sediment organic matter is an important process. PBDEs in the sediments may pose high ecological risks local benthic organisms. The high loading of PBDEs in the rivers supplies the potential contaminant source. Abstract : A good regression of TOC-normalized BDE values with their log K ow in the sediments confirmed that TOC-related sorption of PBDEs dominantly governed their distribution.